Data Science dan Sistem Informasi : Membangun Masa Depan Berbasis Data - Amelda Indra Triana; Afriyanti; Andriyani Ermica Sari; Dian Puspita (Jurnal Pustaka Cendekia Pendidikan, 2025)
This research aims to investigate how the integration of information systems and data science can build a data-driven campus environment to face the challenges of the digital era. The research method used is a descriptive qualitative approach with a literature study of scientific journals, articles, reports, and academic documents, as well as a case study of the implementation of web-based mobile information systems at Institut Bakti Nusantara (IBN). The results show that combining digital information systems with data science techniques increases administrative efficiency, reduces data manipulation, and provides data that can be analyzed for more accurate and predictive decision-making.